2009
DOI: 10.1111/j.1365-2613.2008.00624.x
|View full text |Cite|
|
Sign up to set email alerts
|

Dystroglycan patterns on the prostate of non‐obese diabetic mice submitted to glycaemic control

Abstract: Dystroglycan (DG) is an adhesion protein which plays a crucial role in the maintenance of tissue integrity. Diabetes has been pointed out as a disease which causes harmful effects on prostate function. Therefore, the main objective of this work was to verify DG distribution and structure features in diabetic mice with and without glycaemic control and to relate these parameters to prostate pathogenesis. Thirty mice (Nod and BALB/c) were divided into three groups after 20 days of diabetic state: the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 75 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…Recent studies reported that the β‐DG protein expression significantly reduced in skeletal muscle of Goto Kakizaki rat model of type 2 diabetes. 16 However, there are no relevant studies to observe the changes of dystroglycan protein in neurons under the high glucose toxic.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that the β‐DG protein expression significantly reduced in skeletal muscle of Goto Kakizaki rat model of type 2 diabetes. 16 However, there are no relevant studies to observe the changes of dystroglycan protein in neurons under the high glucose toxic.…”
Section: Introductionmentioning
confidence: 99%